Gamification approach to enhance students’ engagement in Online Distance Learning (ODL) classes / Rosfatihah Che Mat and Sakinah Mat Zin - Mat Zin, Sakinah; Che Mat, Rosfatihah (UiTM Press, 2021)
Online Distanced Learning (ODL) is an online learning method that has been used during outspread of the COVID-19 Pandemic. Conducting ODL can be tough. It is especially challenging when it comes to ensuring the active engagement of students. Many business and management disciplines include the so-called dry or uninteresting content that requires intense concentration and undivided attention from students. Hence, it is a must for business management lecturers to ensure active engagement so that they could assess students’ understanding of the subject matter delivered throughout the Online Distance Learning (ODL) sessions.Thus, the purpose of this conceptual paper is to propose gamification as an approach in assessing student’s understanding. Gamification makes learning more enjoyable experience especially during the pandemic as students undergo ODL lessons at their homes. Theoretically, this paper contributes to the existing literature of gamification in online learning and teaching assessments. Practically, it contributes in increasing the awareness on how the gamification can be used in any subject of business management online classes. Further experimental studies will be conducted to investigate how game-based approach assists in enhancing students’ engagement, understanding of business management subject, as well as how gamification can stimulate excitement and communication skills among students.